2003
DOI: 10.1128/jb.185.3.991-1000.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of SrgA, a Salmonella enterica Serovar Typhimurium Virulence Plasmid-Encoded Paralogue of the Disulfide Oxidoreductase DsbA, Essential for Biogenesis of Plasmid-Encoded Fimbriae

Abstract: Disulfide oxidoreductases are viewed as foldases that help to maintain proteins on productive folding pathways by enhancing the rate of protein folding through the catalytic incorporation of disulfide bonds. SrgA, encoded on the virulence plasmid pStSR100 of Salmonella enterica serovar Typhimurium and located downstream of the plasmid-borne fimbrial operon, is a disulfide oxidoreductase. Sequence analysis indicates that SrgA is similar to DsbA from, for example, Escherichia coli, but not as highly conserved as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 75 publications
(74 reference statements)
0
80
0
2
Order By: Relevance
“…TrbB F and homologues encoded by the three H plasmids contain the thioredoxin C-X-X-C active-site motif, as well as the essential proline residue that is adjacent to the active-site loop. They also contain a hydrophobic or aromatic residue at the third position, which is consistent with a possible role in disulfide bond isomerization (13) Proteins that promote disulfide bond formation have previously been shown to be essential for the proper assembly of a number of periplasmic protein complexes, including the E. coli flagellar apparatus, the enteropathogenic E. coli bundle-forming pilus, the E. coli pap pili, the Klebsiella oxytoca type II secreton, and Salmonella enterica serovar Typhimurium plasmid-encoded fimbriae (15,58). In addition to previous studies on the effect of a dsbA mutation on F piliation as measured by filamentous phage sensitivity and electron microscopy (10), we observed that the mating efficiency of the F plasmid is also affected by the presence of a dsbA mutation in the donor cell and that the addition of DTT further decreases mating ability to undetectable levels.…”
Section: Discussionmentioning
confidence: 78%
“…TrbB F and homologues encoded by the three H plasmids contain the thioredoxin C-X-X-C active-site motif, as well as the essential proline residue that is adjacent to the active-site loop. They also contain a hydrophobic or aromatic residue at the third position, which is consistent with a possible role in disulfide bond isomerization (13) Proteins that promote disulfide bond formation have previously been shown to be essential for the proper assembly of a number of periplasmic protein complexes, including the E. coli flagellar apparatus, the enteropathogenic E. coli bundle-forming pilus, the E. coli pap pili, the Klebsiella oxytoca type II secreton, and Salmonella enterica serovar Typhimurium plasmid-encoded fimbriae (15,58). In addition to previous studies on the effect of a dsbA mutation on F piliation as measured by filamentous phage sensitivity and electron microscopy (10), we observed that the mating efficiency of the F plasmid is also affected by the presence of a dsbA mutation in the donor cell and that the addition of DTT further decreases mating ability to undetectable levels.…”
Section: Discussionmentioning
confidence: 78%
“…2). There was also a correlation between resolution and the number of Yersinia CFU recovered from the sample, with resolution requiring approximately 10 6 Yersinia CFU (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Two genes in the rck operon, pefI and srgA (sdiA-regulated gene), appear to affect the expression and function of the pef operon. The pefI gene encodes a transcriptional regulator of the pef operon, and the srgA gene is a dsbA paralog that specifically catalyzes the oxidation of a disulfide bond in the PefA fimbrial subunit (6,30). Therefore, sdiA may indirectly affect the expression and assembly of plasmid-encoded fimbriae on the surface of the bacterium.…”
mentioning
confidence: 99%
“…Two genes in this operon, pefI (plasmid encoded fimbriae) and srgA (sdiA-regulated gene), affect the expression and function of the pef operon located upstream of the rck operon and involved in the biosynthesis of the Pef fimbriae. pefI encodes a transcriptional regulator of the pef operon, and SrgA is a DsbA paralog that efficiently oxidizes the disulfide bond of PefA, the major structural subunit of the Pef fimbriae (Bouwman et al, 2003). These fimbriae are involved in biofilm formation, adhesion to murine small intestine and fluid accumulation in the infant mouse (Baumler et al, 1996;Ledeboer et al, 2006).…”
Section: Rck Regulationmentioning
confidence: 99%